AN ANALYSIS OF INFLECTIONAL MORPHEMES ERRORS IN WRITING A TEXT BY SECOND-YEAR STUDENT OF MAS TPI SILAU DUNIA - Sholihatul Hamidah Daulay (VISION, 2018)
This study was conducted to find out the students’ errors in using inflectional morphemes that include nouns: singular and plural form especially in regular plural and include verb especially in regular verb to form a simple present tense in third person singular. The aims of this study are to know more about errors made by students in using inflectional morphemes, based on the type of the students’ errors are, error of omission, error of addition, error of misformation and error of misordering. The subjects of this study were 35 students at second-year student of MAS TPI Silau Dunia 2016/2017. The technique of analyzing data of this study was applied by using quantitative descriptive data. The quantitative were taken from a text that students made. The  descriptive were taken from interview. The result of the analysis showed that the average percentage was the error of omission is 58, 33% (42 errors), error of addition is 38,89 % (28 errors), error of misordering is 0%, and error of misformation is 2,78% (2 errors). It means that error of omission is the highest and most dominant from four types of errors. And error caused by intralingual transfer has the higher percentage 54, 05 % (20 causes) than error caused by interlingual transfer 45, 95 % (17 causes). It means that the cause of intralingual transfer was dominantly occurred in the students’ texts.Key Word : Error Analysis, Inflectional Morphemes